2010
DOI: 10.1001/archoto.2010.136
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Animal Model for Wound Healing in Chronic Rhinosinusitis

Abstract: We successfully constructed a model in which wound healing in a setting of chronic eosinophilic inflammation can be studied. In this exploratory pilot, we demonstrated the feasibility of reproducibly wounding the sinonasal cavity of chronically inflamed mice and examining histologic and gene expression effects of the inflammatory response after wounding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…Patients with serum and tissue eosinophilia often require systemic steroids and have significantly higher recurrence and revision rates [15,[21][22][23]. In a previous study of the steroid-eluting implant, revision ESS was indicated in 2.2% (2/90) of cases with use of the Propel stent, which is consistent with the revision rate (1.5%) in the present study [6].…”
Section: Discussionsupporting
confidence: 87%
“…Patients with serum and tissue eosinophilia often require systemic steroids and have significantly higher recurrence and revision rates [15,[21][22][23]. In a previous study of the steroid-eluting implant, revision ESS was indicated in 2.2% (2/90) of cases with use of the Propel stent, which is consistent with the revision rate (1.5%) in the present study [6].…”
Section: Discussionsupporting
confidence: 87%
“…However, Lindsay et al selected Af as a study antigen because Af has been implicated in the pathophysiology of chronic hyperplastic eosinophilic rhinosinusitis and in allergic fungal sinusitis. Subsequently, Tansavatdi et al developed a murine model for wound healing in CRS using Af extracts . This model mimicked the sinus wound healing process rather than the pathogenesis of sinusitis.…”
Section: Resultsmentioning
confidence: 99%
“…They also compared it to wounding the non‐inflamed sinus mucosa in normal mice. As expected, inflamed mucosa showed a stronger response to the needle trauma, therefore, had a higher potential for scarring during wound healing . An allergic sinusitis model in mice was established by Kim et al They induced allergic inflammation in mice with ovalbumin (OVA), an allergenic protein found in chicken egg whites.…”
Section: Introductionmentioning
confidence: 91%